Nilai pendidikan karakter pada tokoh dalam novel Merindu Baginda Nabi: Sebuah kajian sosiologi sastra - Muhimmah, Sulukul (Maliki Interdisciplinary Journal, 2023)
Today, not a few generations of teenagers are experiencing a character education crisis. This study examines how the environment plays a role and influences the formation of positive character in adolescents through the novel Merindu Baginda Nabi. This study aims to find out what character education values exist in the characters and how the environment influences the formation of these characters. This study is a descriptive qualitative research using a sociology of literature approach. The researcher found two opposing characters in this novel, namely the positive character in the main character and the negative character in the comparison character. The six values of positive character education for the main character include (1) Religious; (2) Good morals and ethics; (3) Friendly/communicative; (4) Respect, responsibility, and selflessness; (5) Smart and honest; (6) Humble and forgiving. While the values of character education in the comparison of the main characters include (1) Bad morals and ethics and no religion; (2) Easily aroused and emotional.